Presence of Aflatoxin M1 in Cube Cheeses Produced in Sivas Region - Sema Ağaoğlu (Turkish Journal of Agriculture: Food Science and Technology, 2020)
In this study, the presence and residue levels of aflatoxin M1 (AFM1) were investigated in traditionally produced cube cheeses in Sivas and its region. For this purpose, 90 pieces of cube cheese were used as a material. Cheese samples were collected periodically in November and December 2016 from central sales location and surrounding villages. ELISA technique was applied in aflatoxin analyses. According to the analysis results, AFM1 was detected in total of the cube cheeses. The lowest level of AFM1 was found to be 2.16 ng/kg, the highest was 53.94 ng/kg and the mean was 6.36±0.87 ng/kg. AFM1 level vas determined one cheese sample above to the limit set by European Union.